On-chip single cell funneling operated by microfabricated thermo-responsive hydrogel layers. (22nd May 2015) - Santaniello, Tommaso; Yan, Yunsong; Tocchio, Alessandro; Martello, Federico; Gassa, Federico; Webb, Patrick; Zhao, Weiwei; Tamplenizza, Margherita; Schulte, Carsten; Liu, Yang; Hutt, David; Milani, Paolo; et al.
Abstract: We present a multilayer microfluidic system having a KrF excimer laser micro-patterned thermo-responsive poly-(N-isopropyl)-acrylamide (PNIPAAm) based hydrogel layer integrated as a freestanding component that operates as a temperature-triggered cell isolation actuator for single cell assays applications. When the system is assembled, the size of the laser machined micro-through-hole (entrance diameter is 150  μ m, while exit hole diameter varies from 10 to 80  μ m) can be reversibly modulated as a consequence of the polymer volumetric phase transition induced by heating the device above the critical temperature of 32 °C; as a result of the polymer water loss, the shrinkage of the layer caused the hole to homogeneously shrink, thus reducing its original size to about 40% in the polymer collapsed state. This actuation mechanism was exploited to trap a cellular sample in the shrunken exit hole on the top of the hydrogel layer by applying a negative pressure across the film when the system is brought to 37 °C. Subsequently, the funneling of the trapped cell took place through the orifice when the polymer's natural relaxation at room temperature toward its initial state occurred; the functionality of the device was proved using optical microscopy to monitor MG63 cells as a model cell line during the funneling through the size-modulating structure.